Solid-state fermentation of pineapple waste for nutrient enhancement in animal feed - Khek, Han Wen; Khairul Nizam, Jairin; Rohana, Abu; Noraziah, Abu Yazid; Siti Hatijah, Mortan (Springer Singapore, 2025)
Pineapple waste has a high content of organic compounds and nutrients such as fiber, carbohydrates, and minerals which make the waste can be used as animal feed. Fermented pineapple waste produced higher yields of nutrients as compared to unfermented pineapple waste. Therefore, the objective of this study is to compare different types of fermented pineapple waste (leaves, peels, and crown) and its ratio on nutrient content enhancement for the production of animal feed. To identify the best type and optimal ratio of fermented pineapple waste, measurements were made of the soluble protein, antioxidant, total phenolic content, and reducing sugar. The pineapple waste was fermented with 1.5 g of Rhizopus oligosporus, 1.5 g of spent coffee ground, and trace elements for 3 days at 30℃. Based on the analysis, fermented pineapple leaves with 0.84% (w/v) substrate ratio produced the highest concentration of soluble protein (23.0882 mg/g), antioxidant (58.12%), and reducing sugar (16.2453 mg/g), but have the lowest concentration of total phenolic content (0.0556 mg/g) than pineapple crown and peels. The results also demonstrated an increment of 72, 94, and 95% in total protein, antioxidant, and reducing sugar of the fermented pineapple leaves as compared to unfermented ones. This study demonstrates that solid-state fermentation increased the nutrient contents of the pineapple waste, with pineapple leaves being the best waste to produce highly nutritious animal feed.